Prevalence of Cryptosporidiosis infection among children under 5- years in Cotonou, Benin - OGOUYEMI-HOUNTO, Aurore; Alihonou, Florence; Aholoukpe, Immaculée; BAGNAN, LEHILA; Orekan, Jeanne; Sossa, Blandine (My University, 2017)
Cryptosporidiosis is recognized as one of the leading causes of childhood diarrhea in developing countries, but no data has been published, so far, on the prevalence among children with diarrhea in Benin. The aim of the present study was to assess, for the first time, the prevalence of Cryptosporidium spp. infection in Cotonou, Benin. A prospective study involving children younger than 5 years of age (n = 104) hospitalized or consulted in the paediatric departments of three hospitals between September 2015 and May 2016 was carried out. Cryptosporidium oocysts were detected by means of a smear of sedimented stool stained by the modified Ziehl-Neelsen technique and were found in 5.8% of the studied population. Neither age, non-use of drinking water, nor nutritional status influenced the presence of cryptosporidiosis in the study, but 5 of the 6 children infected were less than two years of age. In conclusion, this first study showed that infection with Cryptosporidium spp. could be a cause of diarrhea in a not insignificant proportion in Cotonou. Studies with larger numbers of patients, conducted for a longer time and in rural areas would be necessary to estimate the real prevalence of cryptosporidiosis and to assess the risk factors.
Keywords: Cryptosporidiosis; prevalence; children; Benin